Improve Initial Numeracy Skills Through Animated Arithmetic Media of Children Aged 5-6 Years at TK Ar-Rochman Pondok Jati Sidoarjo: Meningkatkan Kemampuan Berhitung Permulaan Melalui Media Hitung Animasi Pada Anak Usia 5-6 Tahun di TK Ar-Rochman Pondok Jati Sidoarjo - Anissa Nurlaila; Luluk Iffatur Rocmah (Universitas Muhammadiyah Sidoarjo, 2024)
This study discusses efforts to improve initial numeracy skills through animated arithmetic media at Ar-Rochman Kindergarten Pondok Jati Sidoarjo.The research method used is the Classroom Action Research model of Kemmis and Mc.Taggart with the stagees of planning, implementing, observing, and reflecting. Action subjects totaled 15 children. The activity begins with the Pre-Cycle, then the research process uses 2 stages, namely Cycle I, children study with assistance and Cycle II, children study alone with friends. The results of the study showed that the initial numeracy skills of the Pre-Cycle, Cycle I and Cycle II experienced a significant increase. This proves that there is an increase in children’s initial numeracy skills after using animated arithmetic media. Highlights: The study utilizes Classroom Action Research to assess the impact of animated arithmetic media on initial numeracy skills in a kindergarten setting. The research consists of three stages: Pre-Cycle, Cycle I, and Cycle II, demonstrating a progressive improvement in children's numeracy skills. Findings indicate a significant enhancement in children's initial numeracy skills, affirming the effectiveness of animated arithmetic media in the learning process. Keywords: Counting Starts, Children, Animated Arithmatic Media